Russia Rebounds - Robinson, David (International Monetary Fund, 2003)
Russia Rebounds analyzes Russia's dramatic economic recovery since the country's 1998 financial crisis, emphasizing macroeconomic issues and fiscal and banking sector reforms. The crisis was a massive shock to the system and a considerable surprise to both Russians and foreign investors, who a year before had come to think that the worst of the transition from a centrally planned to a market economy was over. Macroeconomic performance since the crisis has been impressive. The book assesses the contribution of various factors underlying this recovery and highlights key policy challenges to ensure its sustainability.